English at a university language center: Students' favorite topics - Lozada Trimbath, Minnie (2002)
The purpose of this article is to present part of the results of a research study conducted at the Universidad Nacional Mayor de San Marcos by professors Minnie Lazada, Alicia Alanzo and Johanna Reyes. The study considers the perspective of the students of the Language Center of the Faculty of Letters and Human Sciences of the university with respect to the selection of topics in the English courses taught at that institution.